2021
DOI: 10.1097/adm.0000000000000932
|View full text |Cite
|
Sign up to set email alerts
|

Racial-ethnic Differences in Reasons for Misuse of Prescription Medications Among US Adults

Abstract: ObjectivesThis study aims to investigate racial-ethnic differences in reasons for misuse of prescription medications among a nationally representative sample of US adults.MethodsWe analyzed data from the 2015–2019 National Surveys on Drug Use and Health. The study population includes US adults (18–49 years old) who reported misuse of 3 types of prescription drugs (stimulants [n = 6139], sedatives and tranquilizers [n = 5643], and pain relievers [n = 8780]) for 3 reasons: medical-only (eg, to help with pain), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…This finding is consistent with a recent national study that found AAs were less likely than Whites to misuse opioids for purposes of recreation. 37…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding is consistent with a recent national study that found AAs were less likely than Whites to misuse opioids for purposes of recreation. 37…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a recent national study that found AAs were less likely than Whites to misuse opioids for purposes of recreation. 37 There were 3 motivations that had especially high endorsement rates. We discuss the implications of these motivations in more detail here as they likely play a prominent role in shaping OM behaviors among AAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations